Twitter 101 : everything you need to know about Twitter marketing - Dugan, Lauren (FTPress, 2013)
Use Twitter to turbocharge your brand and business, engage users, connect with your industry, capture indispensable customer/prospect data, and build word-of-mouth that translates directly into sales! Twitter 101 is the perfect quick Twitter primer for every entrepreneur and social media marketer, from novices to pros! Leading social media business consultant Lauren Dugan shares dozens of actionable tips, low-cost techniques and powerful tools for transforming Twitter into your all-in-one digital billboard, branded outpost, customer support channel, networking system, web traffic driver, data gatherer, and lead generator. Dugan starts with three revealing Twitter case studies, then walks through mastering the jargon, getting started, defining strategy, optimizing your presence, avoiding beginner's mistakes, and much more. Drawing on personal experience and up-to-the-minute industry research, she helps you time your tweets for maximum impact, follow the right accounts, attract the right followers, learn more about customers and competitors, and use hashtag chats to network at the speed of light. Dugan concludes by listing today's most valuable third-party tools for managing and optimizing your Twitter presence. Lauren Dugan's Twitter 101 : it's the fastest way to transform Twitter into your newest high-profit marketing channel!